2004
DOI: 10.1074/jbc.m400498200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Topoisomerase I and RNA Polymerase I Inhibitors Suggest a Dual Mechanism of Nucleolar/Nucleoplasmic Partitioning of Topoisomerase I

Abstract: Topoisomerase I is mostly nucleolar, because it plays a preeminent role in ribosomal DNA (rDNA) transcription. It is cleared from nucleoli following exposure to drugs stabilizing covalent DNA intermediates of the enzyme (e.g. camptothecin) or inhibiting RNA polymerases (e.g. actinomycin D), an effect summarily attributed to blockade of rDNA transcription. Here we show that two distinct mechanisms are at work: (i) Both drugs induce inactivation and segregation of the rRNA transcription machinery. With actinomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 40 publications
8
42
1
Order By: Relevance
“…This pattern is consistent with other data showing that TOP1 is primarily localized to the nucleolus [23], but shuttles between the nucleolus and the nucleoplasm [24,25], and therefore provides further evidence of the specificity of staining. In some Purkinje neurons however, this pattern was reversed, with the amount of TOP1 being lower in the nucleolus than in the nucleoplasm ( Figure 5B, bottom row).…”
Section: Topoisomerase I Is Also Concentrated In the Nucleus Of Purkisupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern is consistent with other data showing that TOP1 is primarily localized to the nucleolus [23], but shuttles between the nucleolus and the nucleoplasm [24,25], and therefore provides further evidence of the specificity of staining. In some Purkinje neurons however, this pattern was reversed, with the amount of TOP1 being lower in the nucleolus than in the nucleoplasm ( Figure 5B, bottom row).…”
Section: Topoisomerase I Is Also Concentrated In the Nucleus Of Purkisupporting
confidence: 92%
“…Also, our localization of the MRN proteins in human Purkinje neurons is completely consistent with the observations of Jacobsen et al [19]. With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 91%
“…These findings suggest that nucleolar clearance of TDP1 upon prolonged exposure to camptothecin does not stem from a comigration with topo I to the nucleoplasm but rather from the general disintegration and redistribution of nucleolar structures upon prolonged inhibition of rDNA transcription by camptothecin (25). This notion is also supported by the observation that exposure to the topo II-poison VP-16 did not induce nucleolar depletion of GFP-TDP1 (Fig.…”
Section: Tdp1 Decreases Dna Damage Mediated By Topo I and Iimentioning
confidence: 54%
“…These caps have been termed on occasion fibrillar caps as they contain FC proteins. These proteins include: RNA pol I, UBF, TBP, TAF I 63, and TAF I 110 (Reimer et al, 1987;Zatsepina et al, 1993;Jordan et al, 1996) and topoisomerase I (Christensen et al, 2004; Table 3). It has been shown that some nucleolar proteins can be found in both types of cap regions that contain DFC or FC proteins, such as Nopp140 (Chen et al, 1999) and MPP10.…”
Section: Composition Of Lncs and Fibrillarmentioning
confidence: 99%